2019
DOI: 10.1038/s41598-019-43591-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic endothelial cells release small extracellular vesicles loaded with immunostimulatory viral-like RNAs

Abstract: Endothelial cells have multifaceted interactions with the immune system, both as initiators and targets of immune responses. In vivo , apoptotic endothelial cells release two types of extracellular vesicles upon caspase-3 activation: apoptotic bodies and exosome-like nanovesicles (ApoExos). Only ApoExos are immunogenic: their injection causes inflammation and autoimmunity in mice. Based on deep sequencing of total RNA, we report that apoptotic bodies and ApoExos are loaded with divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 78 publications
5
58
0
Order By: Relevance
“…In addition, in glioblastoma multiforme (GBM), an aggressive brain cancer, it was recently reported that components of the spliceosomes contained in ApoExos promote tumor cell proliferation and confer therapeutic resistance to live tumor cells via remodeling of the RNA splicing patterns 67 . Interestingly, ApoExos produced from endothelial cells deliver noncoding RNAs, characterized by sequences rich in uridine and reminiscent of viral RNAs, which can stimulate RIG-I-like receptors and TLRs to induce inflammation 68 , while ApoExos from thymocytes suppresses immune responses by induction of TGFβ in macrophages 69 .…”
Section: Apoptotic Exosomes (Apoexos)mentioning
confidence: 99%
“…In addition, in glioblastoma multiforme (GBM), an aggressive brain cancer, it was recently reported that components of the spliceosomes contained in ApoExos promote tumor cell proliferation and confer therapeutic resistance to live tumor cells via remodeling of the RNA splicing patterns 67 . Interestingly, ApoExos produced from endothelial cells deliver noncoding RNAs, characterized by sequences rich in uridine and reminiscent of viral RNAs, which can stimulate RIG-I-like receptors and TLRs to induce inflammation 68 , while ApoExos from thymocytes suppresses immune responses by induction of TGFβ in macrophages 69 .…”
Section: Apoptotic Exosomes (Apoexos)mentioning
confidence: 99%
“…In recent years, it has been reported that Alu played a role also in the process of inflammation (51,52). The injection of ApoExos containing unedited Alu repeats resulted in inflammation in mice (26). Alu had an influence on the inflammatory response mechanisms of atherosclerosis and coronary artery disease (53).…”
Section: Discussionmentioning
confidence: 99%
“…It can be released from apoptotic cells. Several copies of unedited Alu repeats were found by Hardy et al, contained in exosome-like nanovesicles (ApoExos), which were released by apoptotic endothelial cells (26). Alu has been utilized as a biomarker in many kinds of diseases including cancer (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal exRNAs are recognized by PRRs, such as TLRs, NLRs, and RIG-I-like receptors (RLRs) of their interacting cells and initiate immune response (45). A recent study showed that exosomes released from apoptotic endothelial cells contained enormous amount of diversified viral-like RNAs, which have potential to activate PRRs (46). Exosomes are abundant in microRNAs (miRNAs), small non-coding RNAs which regulate gene expression (44,47).…”
Section: Extracellular Rnasmentioning
confidence: 99%